ENDOSCOPE SYSTEM - HASHIMOTO Susumu (2020)
This endoscope system comprises: a light-emitting unit having first and second light-emitting elements; an imaging element with which the exposure period can be reduced according to the operational period of an electronic shutter when imaging returning light that arises when light emitted from the light-emitting unit is shone onto a photographic subject; an optical filter disposed on a light path from the light-emitting unit to the imaging element; and a light modulation control unit. When the first and second light-emitting elements are made to emit light in a time-shared manner, the light modulation control unit causes the continuous light emission period of the first light-emitting element to vary, thereby adjusting the exposure period when a first returning light is imaged, and causes the continuous light emission period of the second light-emitting element to vary in a period that does not overlap with the operating period of the electronic shutter, thereby adjusting the exposure period when a second returning light is imaged. L'invention concerne un système d'endoscope comprenant : une unité électroluminescente présentant un premier et un deuxième élément électroluminescent; un élément d'imagerie qui permet de réduire la période d'exposition conformément à la période de fonctionnement d'un obturateur électronique lorsque la lumière revenant de l'imagerie, qui survient lorsque de la lumière émise par l'unité électroluminescente, est dirigée sur un objet photographique; un filtre optique disposé sur un trajet lumineux provenant de l'unité électroluminescente vers l'élément d'imagerie; et une unité de commande de modulation de la lumière. Lorsque le premier et le deuxième élément électroluminescent sont réalisés pour émettre de la lumière d'une manière en temps partagé, l'unité de commande de modulation de lumière provoque la variation de la période d'émission lumineuse continue du premier élément électroluminescent, ajustant ainsi la période d'exposition lorsqu'une première lumière de retour est représentée en image, et provoque la variation de la période d'émission lumineuse continue du deuxième élément électroluminescent dans une période qui ne chevauche pas la période de fonctionnement de l'obturateur électronique, ajustant ainsi la période d'exposition lorsqu'une deuxième lumière de retour est représentée en image. 内視鏡システムは、第１及び第２の発光素子を有する発光部と、発光部から発せられた光が被写体に照射された際に生じる戻り光を撮像する際の露光期間を電子シャッタの動作期間に応じて低減可能な撮像素子と、発光部から撮像素子に至る光路上に配置された光学フィルタと、第１及び第２の発光素子を時分割で発光させている場合に、第１の発光素子の連続発光期間を変化させることにより、第１の戻り光が撮像される際の露光期間を調整し、電子シャッタの動作期間に重複しない期間において第２の発光素子の連続発光期間を変化させることにより、第２の戻り光が撮像される際の露光期間を調整する調光制御部と、を有する。